Neurological Wilson’s disease - Almeida , Laryssa Garcia de; Augsten , Ilana Werneck; Raposo, Yan da Silva (Seven Editora, 2023)
We describe the clinical aspects of Wilson's Disease with neurologic features. This disease consists of a disturbance of copper metabolism secondary to a mutation in the gene responsible for encoding the tissue transporter and the enzyme that incorporates the excess element into bile, generating toxic accumulation in the liver, cornea, and central nervous system. Incipient neurological symptoms are subtle and nonspecific, such as difficulty concentrating, coordination, and handwriting changes (for example, micrograph), and begin on average between 20 and 40 years. Laboratory tests reveal impairment of liver function. Specific tests confirm the diagnosis (serum copper and 24-hour urine copper levels elevated and reduced serum ceruloplasmin). Imaging workup can reveal signaled alteration in striatum, and bilateral putamen, midbrain, and pons. It is a rare disease whose epidemiology in Brazil lacks data and complementary tests have reduced specificity. Early diagnosis and treatment have an impact on the neurological prognosis.   DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-136